ICT for the promotion of international business academic programs - Baena, Jose Jaime; Cano, Jose Alejandro; Giraldo, Didier Arley (Opción, 2019)
This article aims to identify the level of use and the benefits offered by information and communication technologies (ICT) for the international business academic programs in the universities. For this purpose, a perception study in 14 universities of Antioquia, Colombia is carried out. Based on the results, it is concluded that websites and social networks such as Facebook and Twitter are the ICT with the highest level of use and development, and they allow the promotion and positioning of the academic programs, facilitate the learning process and communication with stakeholders, and offer job opportunities to students and graduates.